Penilaian Kinerja Sarana Dan Prasarana Daerah Irigasi Rawa Reteh 1 (Rumbai Jaya) Kabupaten Indragiri Hilir (Studi Kasus : Blok B Dan Blok J) - S, Arif Hidayat; Fauzi, Manyuk; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The function and condition of an irrigation network performance system will decrease. This due to the operation of the system for a long period of time. According to PUPR Regulation Number: 14 / PRT / M2015 in Riau Province there is a Swamp Irrigation Area (DIR) Reteh 1 Rumbai Jaya with an area of 3006 ha. The study of DIR's performance has never been done. Assessment of the performance index of DIR Reteh 1 Rumbai Jaya is based on SE Minister of Public Works Number: 02 / SE / M / 2011. In the SE, the assessment includes channels, water structures and protective dikes. Assessment on DIR Reteh Rumbai Jaya obtained the results of the network condition index of 2.16, network functions 44.25% and recommendations for action are rehabilitation; the condition of the protective embankment is good and the recommended action is maintenance. Based on the network function and condition of the protective embankment, the performance of the swamp reclamation network in DIR Reteh 1 Rumbai Jaya is obtained.Keywords : performance index, swamp irrigation, action recommendation